Amides and lignans from Solanum lyratum. (October 2021) - Wang, Xiaowen; Zhao, Yue; Dong, Xueqi; Wu, Xile; Yu, Hai-Yang; Zhang, Li-Hua; Han, Lifeng; Zhang, Yi; Wang, Tao; Wu, Hong-Hua
Graphical abstract: Highlights: Sixteen non-steroidal compounds were isolated and identified from S. lyratum . Structure elucidation of a new lignan and a new natural product were reported. Activities of these isolates against HepG2 cells were reported. Compounds 3 and 6 significantly inhibited the activities of HepG2 cells. Abstract: Sixteen non-steroidal compounds including four amides, six lignans, two sesquiterpenoids and three flavonoids, were isolated from the 80 % ethanol extract of whole plants of Solanum lyratum Thunb. Their structures were assigned based on analyses of extensive spectroscopic data (including MS, 1D/2D NMR and ORD) or comparisons of the NMR data with those reported. Among them, there were a new lignan namely isolariciresinol-9-acetate (5 ), a new natural amide compound ( E )- N -(2-hydroxy-2-(4-hydroxyphenyl)ethyl)-3-(4-hydroxyphenyl)acrylamide (1 ), and two known lignans officinalioside (6 ) and alangilignoside B (7 ), together with other twelve known compounds. 6 and 7 were isolated from S. lyratum for the first time, In addition, in vitro anticancer activities of all these isolates were evaluated by MTT assay and the result indicated that compounds 3 [( E )-3-(4-hydroxy-3-methoxyphenyl)- N -(2-(4-hydroxyphenyl)-2-methoxyethyl)acrylamide] and 6 significantly inhibited the activities of HepG2 liver cancer cells.